Analysis of Procedure for Establishing a Commanditaire Vennotschap (CV) Company at CV Triyunda Surya - Sabda Dian Nuraini Siahaan; Safitri Maya Sari; Nasywa Khalista; Maruli Pardosi; Fizzia Sahbrina (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is motivated by observational data that shows that there are rules for building a business in the form of a commander vennotscap, or in other words, a limited partnership. The aim of this research is to find out how to regulate the behavior of entrepreneurs and consumers within certain limits. The method used is qualitative, obtaining primary data by going directly to the company location. The research was carried out on Thursday, May 4, 2023. The results of this research show that there are still many entrepreneurs who do not really understand the rules of doing business. One of the causes is a lack of knowledge or acquired knowledge, which often results in performance that is not optimal.